THE RELEVANCE OF RESEARCH THE PROGRESS ON THE APPLICATION OF MUSHROOM IN MEAT PRODUCTS PROCESSING - BANDURA, IRYNA; KOSHEL, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In this article, the function of mushrooms and the progress of their application in meat processing were introduced. According to the last research, some types of meat products contain more saturated fatty acids, cholesterol, sodium salt, phosphate, nitrite and other components, and excessive intake of these components may lead to obesity, cardiovascular disease, cancer and a series of diseases. So, the food industry is redesigning existing products or developing new ones that are healthier and more sustainable, and shifting to focus on the application of plant ingredients. Attention is drawn to the fact that more and more studies have been conducted to improve the nutritional and functional properties of food by adding vegetables, beans, cereals, tubers, edible seeds, algae or insects as substitutes for fat, protein and salt. Mushrooms has attracted much attention because of its high nutritional value, wide variety of bioactive compounds, antioxidant effect and health function, and excellent flavor and taste, mushroom can provide exogenous active substances for meat products and improve the nutritional value and functional properties of meat products. The application progress and development prospect of mushroom as fat substitute, protein substitute, salt, phosphate and nitrite substitute, flavor additive and antioxidant in meat products were analyzed. There is a lack of research on the health function of mushroom in meat products, and the potential effects and mechanisms of mushroom applied to meat products on human health and health function need to be further explored in the future. The results showed that the application of mushrooms in meat processing meets people's requirements for green, healthy and functional food industry. Mushrooms are a promising functional additive in meat processing.
Keywords: mushrooms; application; meat products; processing; functional properties